Enhancing GNSS Positioning resilience against strong ionospheric scintillation - Monico, João F. Galera [UNESP]; Patêz, Daniel [UNESP]; Machado, Brian Leite [UNESP]; Rosa, Guilherme P. Santos [UNESP] (Copernicus Publications, 2025)
Abstract. The Global Navigation Satellite System (GNSS) has become an integral component in various applications, offering differing levels of accuracy that span from several dozen meters to mere millimeters. While achieving high precision in positioning is essential, an equally important aspect that must be taken into consideration is the reliability of these results, particularly for applications that demand real-time data processing. Various environments can negatively impact the quality of positioning signals, highlighting the necessity for users to be cognizant of these challenging conditions. In particular, low-latitude regions experience significant interference due to the ionosphere, which plays a pivotal role in determining the effectiveness of GNSS signals. This interference is predominantly attributed to the occurrence of plasma bubbles, which induce scintillation, leading to a noticeable degradation in the quality of GNSS signals. Such conditions can hinder the capability to track certain satellites, potentially resulting in multiple cycle slips that compromise positional accuracy. Therefore, it is crucial to develop and implement strategies that ensure robust GNSS positioning in these affected environments. This paper aims to present a comprehensive analysis of several GNSS Real-Time Kinematic (RTK) evaluations conducted in Brazil, where the impact of scintillation will be systematically assessed alongside positioning results. The study relies on data gathered in both static and kinematic modes to draw conclusions. Furthermore, it will discuss various strategies aimed at mitigating these issues, focusing on enhancing the reliability of GNSS results, which typically involve modifications to the underlying stochastic model used in positioning calculations.